The Effect Of Self-Control On Fear Of Missing Out (FoMO) Among Generation Z Roblox Players In Bekasi City - Cindy Tiara Adinda; Erik Saut H. Hutahaean; Ferdy Muzzamil (Green Publisher, 2026)
This study aimed to examine the effect of self-control on FoMO among Generation Z individuals who play Roblox in Bekasi City. A quantitative approach was employed using simple linear regression analysis with 184 respondents selected through purposive sampling. The research instruments included the Online Fear of Missing Out (ON-FoMO) scale and the Brief Self-Control Scale. The results of the simple linear regression indicated a regression coefficient of −0.895 and a coefficient of determination (R²) of 0.332, with a significance value of 0.001 (p < 0.05), suggesting that self-control accounts for 32.2% of the variance in FoMO, while the remaining variance is explained by other factors not examined in this study. These findings demonstrate that self-control has a significant negative effect on FoMO meaning that self-control can suppress Fear of Missing Out (FoMO) in Generation Z who play Roblox in Bekasi City. However, most respondents were classified in the moderate category, indicating that self-control was not sufficient to reduce FoMO to a low level. This study highlights the importance of strengthening self-control, and future research is recommended to include additional variables such as self-regulation and self-esteem.